(untitled) (Czech Journal of International Relations, 2020)
This Handbook maps the contours of an exciting and burgeoning interdisciplinary field concerned with the role of language and languages in situations of conflict. It explores conceptual approaches, sources of information that are available, and the institutions and actors that mediate language encounters. It examines case studies of the role that languages have played in specific conflicts, from colonial times through to the Middle East and Africa today. The contributors provide vibrant evidence to challenge the monolingual assumptions that have affected traditional views of war and conflict. They show that languages are woven into every aspect of the making of war and peace, and demonstrate how language shapes public policy and military strategy, setting frameworks and expectations. The Handbook’s 22 chapters powerfully illustrate how the encounter between languages is integral to almost all conflicts, to every phase of military operations and to the lived experiences of those on the ground, who meet, work and fight with speakers of other languages. This comprehensive work will appeal to scholars from across the disciplines of linguistics, translation studies, history, and international relations; and provide fresh insights for a broad range of practitioners interested in understanding the role and implications of foreign languages in war.